Association of dietary patterns and degree of food processing with feelings of depression in pregnancy - Nayla de Lourenço Badanai; Daniela Cristina Candelas Zuccolotto; Lívia Castro Crivellenti; Daniela Saes Sartorelli
Abstract Objectives: to investigate the relationship of dietary patterns and degree of food processing with feelings of depression in pregnancy. Methods: cross-sectional study conducted with 784 adult pregnant women in Ribeirão Preto, SP, between 2011 and 2012. Feelings of depression were obtained through a structured questionnaire. Two 24-hour dietary recalls were obtained (24th-39th weeks of gestation) and adjusted through the Multiple Source Method. Four dietary patterns were determined: "Brazilian traditional","snacks", "coffee", and "healthy". Adjusted logistic regression models were used to assess the relationship ofthe tertiles of dietary patterns and energy contribution (% E) of foods according to the degree of industrial processing with feelings of depression (always/most of the time vs. sometimes/never). Results: 12% of the women reported feelings of depression during the pregnancy. Women with greater adherence to "Brazilian traditional"[OR= 0.54 (CI95%= 0.30-0.97)] and "healthy" patterns [0.53 (0.30-0.94)] and with higher % E from minimally processed foods [0.51 (0.28-0.93)] presented a lower chance of feelings of depression. A higher % E from ultra-processed foods [2.39 (1.29-4.41)] was directly associated with the outcome. No associations with the other patterns were found. Conclusions: greater adherence to the"Brazilian traditional" and "healthy" dietary patterns was inversely associated with feelings of depression during pregnancy, possibly mediated by the degree of industrial processing of the foods.